Y-chromosomal and mitochondrial markers: A comparison between four population groups of Italy - Brisighelli, F; Capelli, C; Álvarez-Iglesias, V; Arredi, B; Baldassarri, L; Boschi, I; Dobosz, M; Scarnicci, F; Salas, A; Carracedo, A; Pascali, V (2006)
The investigation into the genetic diversity of humans has become fundamental to the understanding of the pre-history and history of populations, and it is presently addressing crucial issues concerning human evolution that intersect with demographic, cultural and linguistic events. Numerous studies have been recently focused on the Italian Peninsula, and the current set of data regarding this country can now fit into a general frame in which local differences seems to emerge and be interpreted in the context of other cultural and historical knowledge. However, a comprehensive study based on multiple genetic systems and on extensive sampling is still missing. Here we report new data on the Y chromosome and mitochondrial DNA (mtDNA) over a significantly larger Italian sample. In particular we address four geographic sites that in the past have been the theatre of significant events in the framework of Italy's peopling: Latium (central-west), Piceno (central-east), Calabria (south-west) and Messapia (south-east). Concerning the Y polymorphisms, we based our study on STR and SNP markers in order to tackle population events positioned at various stages of the evolutionary history of Italy on the male side, and to account for local differences. In a similar way, mtDNA has been analyzed for the control region and for a selection of informative mtDNA coding region SNPs. The availability of both sets of loci including slow- and fast-evolving markers has enabled us to undertake multiple-level comparisons. We paid special interest to the distribution of genetic variability across our populations and we aimed to compare the mainframe emerging from the haploid male and female inherited loci. Preliminary results provided us with intriguing inferences regarding the prehistory and history of Italy. © 2005 Elsevier B.V. All rights reserved.